Corporate Tax Avoidance and Firm Profitability - Zhu, Naiping; Mbroh, Nancy; Monney, Augustine; Bonsu, Mandella Osei-Assibey (European Scientific Journal, ESJ, 2019)
The idea of trying to reduce an organization’s tax expense is considered as old as the inception of taxation itself as organizations are always trying to exploit loopholes in the complexities of the existing tax system. The traditional motive for such practices is to reduce expenses, thereby increasing the firm’s net profit. In view of this, tax avoidance has always been considered as being in the interest of the shareholders, as it is intended to increase value. However, this view has greatly been questioned in recent researches. Taking data from the annual reports and financial statements of firms listed on the Ghana Stock Exchange (GSE), we empirically tested whether tax avoidance of a firm really translates to increase in value or profitability. Employing a standard Ordinary Least Square regression model, we test our hypotheses using SPSS statistical tools. Our findings confirmed a negative relationship between the tax avoidance measure (ETR) and the measure of profitability (ROA). We conclude that tax avoidance could translate into profitability or value due to the balance of expertise and professionalism exhibited. We recommend that a firm need to have a good corporate governance structure in place, particularly the board structure, since they are in a better position to influence management’s decisions and actions, in order to achieve the intended benefits of such practices.